2014
DOI: 10.1159/000368792
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-205 Is a Candidate Tumor Suppressor that Targets ZEB2 in Renal Cell Carcinoma

Abstract: SummaryBackground: This study aims to characterize the function of downregulated MicroRNA miR-205 in renal cell carcinoma (RCC), and show how the downstream zinc finger E-box-binding homeobox 2 (ZEB2) is negatively regulated by miR-205. Materials and Methods: The expression of miR-205 was detected in RCC and adjacent non-tumor tissues using real-time polymerase chain reaction (PCR). The expression of miR-205 and ZEB2 was detected in RCC cell lines using real-time PCR. The luciferase reporter assay was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
(42 reference statements)
3
27
0
Order By: Relevance
“…We also confirmed that miR-200c expression decreased ZEB1 level in VRCs [53], but we did not observe any effect on miR-200c on ZEB2 expression [54]. VRCs overexpressed miR-205 shown ZEB1/2 downregulation in cancer cells, what is in accordance with previous works [55,56]. Our results, suggests that the molecular mechanisms of miR-200 family on EMT might be cell type specific and more work needs to be done to clarify this.…”
Section: Discussionsupporting
confidence: 92%
“…We also confirmed that miR-200c expression decreased ZEB1 level in VRCs [53], but we did not observe any effect on miR-200c on ZEB2 expression [54]. VRCs overexpressed miR-205 shown ZEB1/2 downregulation in cancer cells, what is in accordance with previous works [55,56]. Our results, suggests that the molecular mechanisms of miR-200 family on EMT might be cell type specific and more work needs to be done to clarify this.…”
Section: Discussionsupporting
confidence: 92%
“…It has been well-established that miRs play important roles in the regulation of cell proliferation, differentiation, apoptosis, migration, invasion, and so forth (911). Moreover, many miRs have been reported to direct target oncogenes or tumor suppressors, and thus play suppressive or promoting roles in human cancers (10,1214).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alteration in miRNA expression is considered to have a part in cancer initiation and progression through regulating the expression of various oncogenes and tumor suppressive genes [7]. It has been reported that miRNA-451a is associated with cell proliferation, migration, and apoptosis in RCC [8], and miRNA-205 is a candidate tumor suppressor by targeting ZEB2 in RCC [9]. Another member of the miRNA family, miR-106a*, is found downregulated in follicular lymphoma [10], but there is no report on its role in RCC.…”
Section: Introductionmentioning
confidence: 99%